2012
DOI: 10.1186/1477-9560-10-3
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding tendency in dual antiplatelet therapy with aspirin/clopidogrel: rescue of the template bleeding time in a single-center prospective study

Abstract: BackgroundPatients with heightened platelet reactivity in response to antiplatelet agents are at an increased risk of recurrent ischemic events. However, there is a lack of diagnostic criteria for increased response to combined aspirin/clopidogrel therapy. The challenge is to identify patients at risk of bleeding. This study sought to characterize bleeding tendency in patients treated with aspirin and clopidogrel.Patients/methodsIn a single-center prospective study, 100 patients under long-term aspirin/clopido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 42 publications
(39 reference statements)
2
11
0
1
Order By: Relevance
“…The prolonged bleeding profile observed herein for acetylsalicylic acid is in agreement with the literature (Beaumont et al 1955;Evans et al 1968;Mielke et al 1969;De Gaetano et al 1971;Praga et al 1972;Altman et al 2012;De Berardis et al 2012;Angiolillo et al 2013;Connolly et al 2013;Field et al 2013;El-Hayek et al 2014;Thomas et al 2014). Similar to our observations, anti-coagulants such as rivaroxaban show higher bleeding profile when compared to a platelet anti-aggregant treatment (Fareed et al 2012;Kennedy et al 2012;Bacchus & Crowther 2013;Scaglione, 2013).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The prolonged bleeding profile observed herein for acetylsalicylic acid is in agreement with the literature (Beaumont et al 1955;Evans et al 1968;Mielke et al 1969;De Gaetano et al 1971;Praga et al 1972;Altman et al 2012;De Berardis et al 2012;Angiolillo et al 2013;Connolly et al 2013;Field et al 2013;El-Hayek et al 2014;Thomas et al 2014). Similar to our observations, anti-coagulants such as rivaroxaban show higher bleeding profile when compared to a platelet anti-aggregant treatment (Fareed et al 2012;Kennedy et al 2012;Bacchus & Crowther 2013;Scaglione, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…In this work, we also challenged the Drabkin modified method by evaluating a platelet anti-aggregant (acetylsalicylic acid) and an anti-coagulant drug (rivaroxaban). Our results showed a higher bleeding profile for both platelet anti-aggregant and anti-coagulant drugs in comparison with the controls, in accordance with the reports using the traditional immersion method with water (Altman et al 2012;De Berardis et al 2012;Angiolillo et al 2013;Connolly et al 2013;Field et al 2013;El-Hayek et al 2014;Thomas et al 2014). However, it is difficult to establish a fair comparison between our findings and the previous reports as none of them quantified total Hb loss through a concentration-dependent curve.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, the patient was on cilostazol, an antiplatelet agent, and the lesion appeared following a history of trauma. Older patients with a long‐term history of antiplatelet agent or anticoagulant use have an increased bleeding tendency following trauma . Late‐onset haemorrhagic events in the brain or other internal organs are commonly observed in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these indications are appropriate because previous data showed that BT results were correlated with bleeding from these acquired platelet dysfunctions. Altman et al [16] reported the correlation between results of template BT and degree of platelet inhibition as well as bleeding episodes in patients who were under aspirin and clopidogrel treatment. About evaluation of bleeding in patients with renal failure, previous data found that BT was a useful test to evaluate bleeding risk in uremic patients [17,18].…”
Section: Discussionmentioning
confidence: 99%